Basics of metal mining influenced water - McLemore, Virginia T. (Management technologies for metal mining influenced water ;, 2008)
Basics of Metal Mining Influenced Water is a must read for planners, regulators, consultants, land managers, students, researchers, or others concerned about the environmentally sound management of metal mine wastes and drainage quality. The first of a series of six handbooks on technologies for managing metal mine and metallurgical process draining, this book offers a unique, comprehensive perspective on the subject. Unlike other texts that focus primarily on acid drainage from coal mines, the authors examine both acidic and neutral pH waters that can be hazardous to the environment. Planning.